(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article examines the development of entrepreneurial skills among female students in Uzbekistan, with particular emphasis on the design field. It highlights international and national initiatives promoting women’s entrepreneurship, referencing the 2011 UNESCO congress in Geneva and Uzbekistan’s state policies such as the Action Strategy 2017–2021 and the “Every Family is an Entrepreneur” program. The study identifies key qualities required for female student entrepreneurs, including creativity, innovation, independence, organizational skills, and motivation, with motivation recognized as the primary driving factor. Evaluation criteria encompass psychological, intellectual, and procedural aspects, as well as independence diagnostics based on S. Grinshpun’s methodology, which considers moral maturity, competence, communication, creativity, and self-control. Practical reforms, new curricula, and modern educational standards further support the integration of entrepreneurship into higher education. The conclusion emphasizes that Uzbekistan’s higher education institutions, especially in design-related disciplines, provide favorable conditions and effective pedagogical systems for fostering female entrepreneurship.